Inclusion, parental stress and social support in families of children with Special Educational Needs - Felizardo, Sara (2017)
This study is part of a current line of research on the potential of social support in families of children with Special Educational Needs (SEN) and the link between social support and health outcomes and parental well-being (Dunst, Trivette & Jodry, 1997). In this context, social support can be defined as the set of resources provided to an individual or group, for members of their social network. Under the inclusive paradigm, the research aims: i) to compare groups of parents of children with and without special education needs, with regard to the variables social support and parental stress; ii) understand the relationships between stress and social support variables; iii) to analyze the predictive dimension of social support on parental stress. This is a non-experimental and cross-correlated study with a non probabilistic convenience sample of 301 parents or caregivers. Data were collected in groups of schools and institutions of support for disabled children on the district of Viseu. The gathering instruments were the Parental Stress Index (Adidin & Santos, 2003), the Social Support Questionnaire – short version (Pinheiro & Ferreira, 2001); Parental Questionnaire (sociodemographic, family and school data). Both groups of parents show significant differences in all total and partial evaluations of parental stress and partly on social support (satisfaction with support), but not in the availability of social networking, Regression analysis for parental stress enhances the predictive value of social support, behaviour problems and family problems. Conclusion: Social support arises as a variable that has significant relationships with parental stress, emerging with a strong predictive power. This line of research should be continued in order to analyze the role of social support as mediator variable of parental stress and well-being in families of children with special education needs.